2015
DOI: 10.1021/jacs.5b04899
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Borylation of Primary Benzylic C–H Bonds without a Directing Group: Scope, Mechanism, and Origins of Selectivity

Abstract: Primary benzylic boronate esters are useful intermediates in organic synthesis, but these reagents cannot be prepared by hydroboration. The benzylic C-H borylation of methylarenes would be a method to form these products, but such reactions without neat methylarene or a directing group are unknown. We report an approach to divert the borylation of methylarenes from aromatic positions to benzylic positions with a silylborane as reagent and a new iridium catalyst containing an electron-deficient phenanthroline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 46 publications
6
89
4
1
Order By: Relevance
“…At 0.2 mol% Co loading, UiO-Co afforded secondary and tertiary benzylic boronate esters from ethylbenzene and isopropryl benzene, respectively, in 100% conversion, and the selectivities for the benzylic products over the aryl products were ∼4:1 (entries 12–13, Table 1). These results contrast with analogous reactions reported with a chemoselective homogeneous iridium catalyst that is active for borylation of only primary benzylic C−H bonds33.…”
Section: Resultscontrasting
confidence: 96%
“…At 0.2 mol% Co loading, UiO-Co afforded secondary and tertiary benzylic boronate esters from ethylbenzene and isopropryl benzene, respectively, in 100% conversion, and the selectivities for the benzylic products over the aryl products were ∼4:1 (entries 12–13, Table 1). These results contrast with analogous reactions reported with a chemoselective homogeneous iridium catalyst that is active for borylation of only primary benzylic C−H bonds33.…”
Section: Resultscontrasting
confidence: 96%
“…48 Selective borylation at the benzylic position was possible with an iridium/phenanthroline system when silylborane was used as the borylating agent to deliver 10a. 47 In contrast, the robust Pt catalyst developed in the current study was found to be insensitive to the steric hindrance suffered by the other systems to allow for the exclusive CH borylation of 9 at its 3-position to provide 10b. The current platinum-catalyzed borylation was found to be amenable to scale up, as exemplified by the gram-scale synthesis of 3k, which could be used as a versatile building block for the introduction of different groups (Scheme 6).…”
mentioning
confidence: 57%
“…Direct borylation of arenes, alkenes, and alkanes to form the corresponding boronic acids or boronates has been developed as one of the most fundamental methodologies in modern organic synthesis, particularly when the products are important raw materials for cross‐coupling reactions in forming new C–C bonds . Catalysts based on iridium complexes, such as [Ir(µ‐X)(cod)] 2 /dtbpy (cod = 1,5‐cyclooctadiene, dtbpy = 4,4′‐di‐ t Bu‐2,2′‐bipyridine, X = Cl, OMe), have demonstrated high performance in direct borylation reactions.…”
Section: Application Of Ionic Liquids In Synthesismentioning
confidence: 99%